2011
DOI: 10.1371/journal.pone.0016300
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Trends in the Impact Factor of European versus USA Biomedical Journals

Abstract: BackgroundThe impact factors of biomedical journals tend to rise over time. We sought to assess the trend in the impact factor, during the past decade, of journals published on behalf of United States (US) and European scientific societies, in four select biomedical subject categories (Biology, Cell Biology, Critical Care Medicine, and Infectious Diseases).MethodsWe identified all journals included in the above-mentioned subject categories of Thomson Reuters Journal Citation Reports® for the years 1999, 2002, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…We also observed an influence of journals‘ countries of origin and the languages used besides English on the results: journals originating in North America tend to have a higher IF, followed by journals from Northern and Western Europe. However, European journals may catch up with America in the future [7]. Most likely, our findings can be ascribed to the number of potential readers that depend on the article language, the country of origin, and the historically developed structures and reputation of medical societies and journals.…”
Section: Discussionmentioning
confidence: 95%
“…We also observed an influence of journals‘ countries of origin and the languages used besides English on the results: journals originating in North America tend to have a higher IF, followed by journals from Northern and Western Europe. However, European journals may catch up with America in the future [7]. Most likely, our findings can be ascribed to the number of potential readers that depend on the article language, the country of origin, and the historically developed structures and reputation of medical societies and journals.…”
Section: Discussionmentioning
confidence: 95%
“…have recently shown that journals published on behalf of European scientific societies in 4 select biomedical categories increased, during 1999–2008, their IF more than the corresponding US journals (published on behalf of US scientific societies) . The authors interpreted their findings as potentially indicative of the financial effort of the European Union to close the gap in research output with the USA, yet they also point out to other factors that may have increased the permeation of European journals in the worldwide scientific community, such as the possibility that journals published in a country language have changed it into English, or the expansion of scientific databases, such as Scopus, that comprise a greater amount of European journals than PubMed . On the basis of these findings, if we speculate that 10–15 years ago, European journals lagged behind US ones in COI policies (and overall journal quality and editorial policies), one may hypothesise that, currently, European journals have also closed the gap in these policies with US journals.…”
Section: Discussionmentioning
confidence: 99%
“…Emerging evidence suggests that periodicals with affiliation and endorsement of relevant professional societies get an advantage and attract more citations (54). The journal affiliation to a professional society is advantageous in terms of maintaining flow of relevant submissions from the membership and continuous support of the scientific community, both valued by prestigous indexing services.…”
Section: Emerging Alternative Factors Of the Impactmentioning
confidence: 99%